(untitled) (Південний архів (історичні науки), 2021)
The article is devoted to analyzing the Kherson Jewish community in the middle of the XIX century. The presentation is based on a comprehensive study of the two-volume work of Alexander Schmidt, "Materials for Geography and Statistics of Russia. Kherson province". Source criticism shows that the work contains a significant amount of reliable information on the history of individual ethnic groups of Kherson in the mid-nineteenth century, which allows us to consider it as a reliable historical source. The primary attention author pays to the issues of the demographic and social structure of the Jewish community. The number, sex component, population movement, social status were analyzed. The role of Jews in the city’s economy, especially in the functioning of a market economy, is highlighted. The article shows the peculiarities of the culture and way of life of the Kherson Jews, their interaction and relations with other ethnic groups. The author proves that the XIX century was the time of the highest rise, the acme in the history of the Jewish community of Kherson, and the Jews significantly determined the city’s face. Their number grew faster than other ethnic groups, they predominated among the wealthiest Kherson citizens, and their business activities contributed to the progress of Kherson.